2018
DOI: 10.1038/s41598-018-28828-6
|View full text |Cite
|
Sign up to set email alerts
|

Itching and its related factors in subtypes of eczema: a cross-sectional multicenter study in tertiary hospitals of China

Abstract: Itching is a leading symptom of eczema or dermatitis and has a great impact on patients’ lives. Previous studies on itching have focused mostly on atopic dermatitis (AD). A cross-sectional multicenter study was conducted among outpatients with eczema from 39 tertiary hospitals in mainland China from July 1 to September 30, 2014. This work elaborates on itching in different types of eczema. Itching was very common (97%, 8499/8758) in outpatients with eczema. The severity of the itch increased with age and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…14 In addition, the severity of pain in patients with genital eczema was also higher than that in those with hand eczema (mean VAS, 2.6 ± 3.0). 14 Moreover, the study by Wang et al 15 found that 11.5% of patients with hand eczema and 6.9% of patients with seborrheic dermatitis suffered from severe pruritus, while a higher proportion of severe pruritus in patients with genital eczema (22.22%) was observed in this study. Concerning DLQI, patients with genital eczema showed a poorer QOL than patients without genital eczema overall.…”
Section: Discussionsupporting
confidence: 56%
“…14 In addition, the severity of pain in patients with genital eczema was also higher than that in those with hand eczema (mean VAS, 2.6 ± 3.0). 14 Moreover, the study by Wang et al 15 found that 11.5% of patients with hand eczema and 6.9% of patients with seborrheic dermatitis suffered from severe pruritus, while a higher proportion of severe pruritus in patients with genital eczema (22.22%) was observed in this study. Concerning DLQI, patients with genital eczema showed a poorer QOL than patients without genital eczema overall.…”
Section: Discussionsupporting
confidence: 56%
“…The pruritus may be so intense that it interrupts daily activities and disrupts the ability to fall or stay asleep. 16 Histologically, biopsy specimens show psoriasiform spongiotic dermatitis with mononuclear cells contained in the vesicles. Interstitial edema and perivascular lymphohistiocytic infiltrates are evident.…”
Section: Clinical and Histopathological Features Of Id Reactionsmentioning
confidence: 99%
“…In this study, atopic dermatitis was diagnosed according to the Williams diagnostic criteria [10]. Widespread eczema refers to the presence of eczema at multiple sites at the same time [11,12].Other types of eczema, including allergic contact dermatitis, asteatotic eczema, autosensitization eczema, dyshidrotic eczema, hand eczema, irritant contact dermatitis, neurodermatitis, nummular eczema, photocontact dermatitis, seborrheic dermatitis, stasis dermatitis, unclassified eczema, and widespread eczema, were diagnosed on the basis of clinical characteristics and medical history according to the International Classification of Diseases-(ICD-) 10 [13][14][15]. Suspected secondary bacterial infection of dermatitis was clinically evaluated.…”
Section: Data Collection and Diagnosismentioning
confidence: 99%